Strategi Mitigasi dan Adaptasi Bencana Banjir di Distrik Nabire Kabupaten Nabire - Husain Husain; Johnson Siallagan; Janviter Manalu; Auldry F. Walukow; Basa T. Rumahorbo (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
Nabire Regency, located in Central Papua Province, is among the regions highly vulnerable to flooding due to persistent and intense rainfall throughout the year. Flood disasters generate multifaceted impacts, including economic losses caused by property damage and business disruptions, social issues such as health problems and psychological distress, and environmental degradation in the form of erosion and water pollution. This study aims to formulate mitigation and adaptation strategies for flood disasters by analyzing community perceptions and evaluating existing measures. The research employs the Likert Scale method to assess public perception and the Analytic Hierarchy Process (AHP) approach to determine the most effective strategies for mitigation and adaptation. The findings reveal that the community possesses a solid understanding of flood events and acknowledges the necessity of implementing mitigation and adaptation efforts. The AHP analysis indicates that the Regional Disaster Management Agency (BPBD) plays a crucial role in executing flood management strategies, particularly within the environmental management domain. The primary recommended strategy is environmental planning and management. Through an integrated and sustainable approach, flood risks are expected to be mitigated more effectively, minimizing adverse impacts on both the community and the environment in Nabire Regency.